2020
DOI: 10.1021/acs.orglett.0c01513
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,4-Fused Tricyclic Indoles through Cascade Carbopalladation and C–H Amination: Development and Total Synthesis of Rucaparib

Abstract: 3,4-Fused tricyclic indole scaffolds are ubiquitous in bioactive natural products and pharmaceuticals. A new protocol for the synthesis of 3,4-fused tricyclic indoles has been developed through cascade carbopalladation and C–H amination with N,N-di-tert-butyldiaziridinone. The protocol allows access to a range of 3,4-fused tricyclic indoles, including those containing various linkers and fused with medium-sized rings. Rucaparib can be synthesized via this reaction, providing an advantageous synthetic method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Cascade enzyme reactions have been utilized with different purposes, especially in the development of a more-efficient synthesis of chemical compounds, such as bioactive oligosaccharides, glycosylated molecules, or amoniacid derivatives [21][22][23][24][25][26].…”
Section: Enzymatic Cascade Processesmentioning
confidence: 99%
“…Cascade enzyme reactions have been utilized with different purposes, especially in the development of a more-efficient synthesis of chemical compounds, such as bioactive oligosaccharides, glycosylated molecules, or amoniacid derivatives [21][22][23][24][25][26].…”
Section: Enzymatic Cascade Processesmentioning
confidence: 99%
“…Moreover, a range of macrocyclic 3,5-and 3,6-fused indoles can be also created, which largely expands the scaffold diversity. Shortly after this work published, two independent works (Cheng et al, 2020;Zhang et al, 2020) were reported using similar catalytic systems for synthesis of 3,4fused indoles by using N,N-di-tert-butyldiaziridinone as the Nsource. By employing this cascade cyclization, Cheng et al (2020) accomplished a concise synthesis of rucaparib, which is a PARP-1 inhibitor and a Food and Drug Administration-approved cancer medicine.…”
Section: Construction Of Polycyclic Heterocycles Fused Pyridines and mentioning
confidence: 99%
“…Almost at the same time, Zhang and co-workers reported a similar tricyclic indole synthesis by applying a comparable strategy, but using N,N-di-tert-butyldiaziridinone 49 as the amination reagent. 52…”
Section: Short Review Synthesis Scheme 28 Synthesis Of Spirocyclic Prmentioning
confidence: 99%